Contibuição para a modelização dinâmica do processo de decantação de biodiesel - Brásio, Ana S. R. (2010)
This paper aims to contribute to the development of a dynamic model to describe the process of separation between biodiesel and glycerol with the equipment most commonly used for this purpose: the gravitational settlers. After a thorough review of previous works in modeling gravitational settlers, a complex model has been developed based on population balances, that considers a mixer followed by a decanter. The mixer corresponds to the reaction vessel where the biodiesel, which is being produced by chemical reaction, instantaneously gets dispersed into small droplets by mechanical means. The model predicts the distribution of drops in the mixer. This is a transient state model consisting of a set of integro-differential and algebraic equations. The decanter was addressed only in steady-state, for lack of time to take the study further. The corresponding model is also composed of a set of integro-differential and algebraic equations and predicts the evolution of the height of the band dispersion along the steady-state settler. Different implementations of the model were made and their performances compared. Using a simulation framework based on Octave/C++, the computation times encountered proved to be small relative to the time of Ribeiro (1994). This is still a preliminary work, requiring, for example, an appropriate model for the system biodiesel–glycerol–alcohol. The modeling of the mixer-settler suggested here has not yet been applied to the process of biodiesel production, showing the originality and innovation of the present work. The implementation of the decanter model is not yet complete, since there are currently some significant discrepancies between the behavior provided by the current implementation and those published previously by other authors. The longitudinal profiles of the volume fraction and of the velocity of the droplets were similar to those presented by Ruiz (1985). The profiles obtained for the height of the dispersion band and the average volume of drops still present some discrepancies relatively to the work of Ruiz (1985), although the values are of the same magnitude. The results predicted by the mixer model present a good degree of agreement with those presented by Ruiz (1985). The tests showed that the model, in the presence of coalescence and breakage phenomena between drops, predicts well the evolution of the volume distribution of the population of drops. In presence of coalescence, the volume of the droplets tend to increase while their number tend to decrease. The phenomena of breakage leads to a decrease in the volume drops, and to an increase of their number. In the mixer, due to the mechanical action of the blades, the main phenomena occurring is the breakage, which reduces the volume average drop over time. The results were very close to those obtained by Ribeiro (1994), and it can be concluded that the model captures well the behavior of the mixer.